Example–conclusion map in teaching simple interest: A lesson study - Fleur De Cory Apasen Ngiwas; Daisy Lyn F. Mariano; Jayson G. Barsana; Michelle P. Cruz; Levi Elipane (International Journal of Evaluation and Research in Education (IJERE), 2022)
This study investigated the utilization of example-conclusion map (ECM), a tool in teaching simple interest to senior high school in a university in the Philippines. With the purpose of presenting the topic in a more relevant way to learners under the Accountancy and Business Management strand, the researchers engaged in a lesson study. The following issues emerged: i) Contextualizing ECM links the topic to real life problems; and ii) Strategizing with ECM provides opportunities to engage in deep and meaningful thinking given an otherwise technical/mechanical topic. Students were able to deduce conclusions and create their own examples. The learners were given the opportunities to discover the formula and establish how simple interest is computed through the collaboration. Through the facilitation of the teacher using ECM as a pedagogy, substantive conversations and clear understanding of the topic were evident. Contextualized examples in teaching simple interest still needed to be improved. It is concluded that teaching simple interest through ECM is effective. It also facilitates a transformative topic that will not just underpin concepts on computations and algorithms, but utilize critical thinking skills to analyze profound issues the community deals with like issues on social justice, loaning, and investing.